A Novel Radiographic Sign and a New Classifying System in Mastoiditis-Related Epidural Abscess. Issue 8 (September 2015) - Horowitz, Gilad; Fishman, Gadi; Brenner, Adi; Abu-Ghanem, Sara; Derowe, Ari; Cavel, Oren; Fliss, Dan M.; Segev, Yoram
<x xml:space="preserve">Abstract</x> Objective To describe a novel radiographic sign ("halo") and a new classification method of an evolving perisigmoid epidural abscess and present its correlation with intraoperative findings. Study Design Retrospective and prospective cohort study in a tertiary academic children's hospital. Methods The retrospective arm (15 children) was conducted between 1998 and 2007 and the prospective arm (11 children) between 2008 and 2013. The computerized tomographic appearance of the perisigmoid region was classified into four groups: Class I, normal; Class II, smooth halo; Class III, nodular halo 4 mm or less in diameter; and Class IV, gross nodular halo more than 4 mm in diameter. Intraoperative findings of the perisigmoid region were compared with the preoperative scan results. Results The correlation between preoperative imaging and intraoperative findings of the retrospective arm was highly significant (p = 0.007). The correlation between the preoperative imaging studies and intraoperative findings of the prospective arm was also highly significant (p = 0.005). The interobserver agreement for the proposed classification method was high (Cohen kappa score, 0.76; weighted kappa score, 0.84). Conclusion A novel radiographic sign ("halo") and a new classification method for an evolving perisigmoid epidural abscess in acute mastoiditis are described. A thin and smooth halo sign is not indicative of a true abscess formation. Gross perisigmoid granular changes, however, are highly suggestive of an epidural abscess that warrants surgical intervention.